Common Issues Among Asthma, Epilepsy, and Schizophrenia: From Inflammation to Ca2+/cAMP Signalling - Bergantin, Leandro B. (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2021)
Background: A large amount of evidence has described that asthma may be associated with a high epilepsy risk, and epilepsy may be linked with high asthma risk, especially among children and individuals in their 30s. Curiously, asthma has also been associated with an increased risk for schizophrenia. Most interestingly, a bidirectional link between schizophrenia and epilepsy has also been established and has been of interest for many years. Objective: Bearing in mind the experience of our group in the field of Ca2+/cAMP signalling pathways, this article discussed, beyond inflammation, the role of these signalling pathways in this link among epilepsy, asthma, and schizophrenia. Methods: Publications involving these signalling pathways, asthma, epilepsy, and schizophrenia (alone or combined) were collected by searching PubMed and EMBASE. Results and Conclusion: There is a clear relationship between Ca2+ signalling, e.g. increased Ca2+ signals and inflammatory responses. In addition to Ca2+, cAMP regulates pro- and anti-inflammatory responses. Then, beyond inflammation, the comprehension of the link among epilepsy, asthma, and schizophrenia could improve the drug therapy.
Keywords: schizophrenia